Analysis Of The Application Of Customary Fines In Resolving Cases Of Violent Land Grabbing Under Timorese Customary Law In Taebenu District, Kupang Regency - Humau, Rody Marsela; Medan, Karolus Kopong; Wilhelmus, Bhisa Vitus (Fakultas Hukum Dehasen, 2026)
Customary fines are sanctions imposed on individuals or groups who violate customary norms or traditional rules, with the aim of restoring the disturbed balance and serving as a means of social control when problems arise within a community. In Timorese customary society, customary fines continue to play an important role as a mechanism for dispute resolution, including in cases of land grabbing accompanied by violence. This study aims to analyze the application of customary fines in resolving cases of violent land grabbing under Timorese customary law in Taebenu District and to identify the factors influencing their effectiveness. This research employs an empirical legal method with a sociological juridical approach. Data were collected through interviews with customary leaders, village officials, perpetrators, and victims, and were supported by a literature review of relevant legal materials. The findings indicate that the imposition of customary fines is carried out through customary deliberation mechanisms involving customary leaders, community leaders, village authorities, and the disputing parties. The customary sanctions generally consist of a combination of rice, pigs, and cash, with the amount determined according to the level of fault and the impact of the act committed. Substantively, the application of customary fines functions not only as a sanction but also as a means of restoring social relationships, maintaining community balance, and achieving peaceful conflict resolution. Normatively and culturally, this mechanism continues to be respected and practiced by the community as an integral part of Timorese customary values. The effectiveness of customary fines is supported by strong local wisdom, community respect for customary authorities, the moral pressure and social shame generated by customary sanctions, and the enduring culture of deliberation within the community. However, several obstacles remain, including the increasing economic value of land, unclear land boundaries and inheritance status, imbalance between the imposed fines and the material losses suffered by victims, and the influence of modernization that encourages some individuals to seek resolution through formal state law. These factors indicate that customary fines have not yet fully prevented the recurrence of violent land grabbing cases.